Kelayakan Bisnis Penggilingan Padi Minhajul Abidin Desa Telaga Bidadari, Hulu Sungai Selatan - Annisa Annisa; Norbaiti Norbaiti; Walinasifa Walinasifa; Norkhadizah Makkiah; Muhammad Firliadi Noor Salim (Universitas 45 Surabaya, 2025)
Agriculture serves as a primary sector of Indonesia's economy, where rice milling management plays a vital role in enhancing post-harvest productivity and supporting food security. This study aims to analyze the management of a rice milling factory in Hulu Sungai Selatan City by examining financial, environmental, human resource (HR), and market-marketing aspects. A qualitative method with a case study design was employed, involving in-depth interviews with the factory manager. The findings reveal efficient financial management based on Islamic principles, sustainable waste management practices, HR strategies focused on training and effective communication, and direct marketing strategies that successfully reach local consumers. In conclusion, effective rice milling management enhances operational performance and contributes to the local economy, despite facing challenges in market dynamics and resource limitations.